1999
DOI: 10.1007/s003300050896
|View full text |Cite
|
Sign up to set email alerts
|

Wernicke encephalopathy: MR findings in two patients

Abstract: Wernicke encephalopathy is a serious neurologic disorder caused by vitamin-B1 or thiamine deficiency. In the literature the characteristic symmetric paraventricular lesions of Wernicke encephalopathy are hyperintense on T2-weighted sequences spin-echo (SE) and enhance on T1-weighted SE sequences after intravenous gadolinium administration in the acute phase. We present two patients in the acute phase of Wernicke encephalopathy with special reference to the MR imaging. One of our reported cases is special becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 17 publications
0
16
1
Order By: Relevance
“…In our patient, ophthalmoplegia and confusion rapidly improved after thiamine supplementation, although cerebellar symptoms and Korsakoff's syndrome persisted. MRI intensity changes around the third and fourth ventricles, Sylvian aqueduct, mammillary bodies, medial thalami, and tectum are typical of Wernicke's encephalopathy 8,9. However, in our patient the cerebellar lesion was more prominent than those in the thalamus, periaqueductal area, mamillary body, and tectum.…”
Section: Discussioncontrasting
confidence: 50%
“…In our patient, ophthalmoplegia and confusion rapidly improved after thiamine supplementation, although cerebellar symptoms and Korsakoff's syndrome persisted. MRI intensity changes around the third and fourth ventricles, Sylvian aqueduct, mammillary bodies, medial thalami, and tectum are typical of Wernicke's encephalopathy 8,9. However, in our patient the cerebellar lesion was more prominent than those in the thalamus, periaqueductal area, mamillary body, and tectum.…”
Section: Discussioncontrasting
confidence: 50%
“…The incidence in random autopsies is reported to be 0.8-2% [16,17]. The classic clinical triad of WE including ocular dysfunction (nystagmus, conjugate gaze palsies, ophthalmoplegia), ataxia and altered mental status is only observed in 30% of patients [18]. If left untreated, patients may develop Korsakoff psychosis, a form of severe amnesia, characterised by memory loss and confabulation, which may occur without other symptoms of WE.…”
Section: Wernicke Encephalopathymentioning
confidence: 97%
“…The involvement of the caudate nuclei, in particular of the capita, may be due to their adjacent position to the lateral ventricles. Opdenakker et al reported a case of hemorrhagic focus in the caput of the right nucleus caudatus of a patient with WE [75]. According to Zhong et al, the presence of lesions of the caudate nuclei, frequently observed in patients in comatose state, is a sign of pathologic evolution [76].…”
Section: Mr Imaging Findingsmentioning
confidence: 99%